Allocation of Taxing Powers - King, David (OECD Publishing, 2007)
Sub-central taxes are needed because sub-central governments spend large sums. This article discusses some key issues in sub-central taxation from an economist's perspective, including the scale and role of sub-central governments, their main revenue sources, and questions of equity, tax sharing, economic management and accountability. A more detailed discussion explores the relative shares of domestic taxes and business taxes